Navigating the contested terrain of teacher education policy and practice: Introduction to the special issue - Aydarova, Elena; Berliner, David C. (Education Policy Analysis Archives, 2018)
In the policy climate where various actors claim to have the solutions for the enduring challenges of teacher education, policy deliberations sideline certain voices. This introduction to the special issue explores policy contestations surrounding teacher education and highlights some of the perspectives overlooked by policy debates. It lays out new priorities for the teacher education community to ensure that the profession’s collective voice would be heard by policy-makers and by the public at large.